Political economy: Success or failure? - Bruno S. Frey (Center for Economic Studies and ifo Institute (CESifo), 2011)
Political Economy and Public Choice have studied the interactions between the economy and the polity for over 60 years now. The present paper endeavours to provide a critical discussion of this literature and its achievements. In particular, it starts with the different approaches based on empirically tested or politometric models, and it then proceeds to discuss different studies of the effects that particular rules of the game have on politico-economic outcomes. The third part will deal with studies that take institutions to be endogenous and aim at explaining why particular institutions emerge. Finally, the question whether political economy has been a success or a failure will be tackled. While the success in terms of the position gained in economic research and teaching is undeniable, a look at one of the most thriving recent areas of economics, namely happiness research, will reveal that fundamental lessons all too often remain disregarded.
Keywords: D72; 330; Public Choice; Institutionalismus; Theorie